Influence of marital status on overall survival in patients with ovarian serous carcinoma: Finding from the surveillance epidemiology and end results (SEER) database - Luo, Pei; Zhou, Jianguo; Jin, Su Han; Qing, Ming Song; Ma, Hu (Journal of Ovarian Research, 2019)
Objective: This study is to investigate the relationship between marital status and prognosis of patients with ovarian serous carcinoma. Results: We performed data analysis from 19,276 patients identified from the SEER database of the National Cancer Center of the United States. 57.8% of the patients were married, 13.0% unmarried, and 29.2% separated/ divorced/widowed (SDW). The median overall survival time ofthe unmarried group and the married group are 48 months and 52 months respectively. Univariate Cox regression analysis showed that the patients with serous ovarian cancer in the unmarried group resulted in a hazard ratio (HR) of 1.14 (95% CI: 1.08-1.19%; P < 0.001), comparing to SDW group with a HR of 1.02 (95% CI: 0.98-1.19%; P = 0.26). However, the SDW group was not statistically significantly different from the married group. (median 32 vs 52 months). Multivariate Cox regression analysis presented the unmarried group leading to a HR of 1.05 (95% CI: 1.00-1.11%; P = 0.05), and the SDW group was not significant with a HR of 0.99 (95% CI: 0.95-1.03%; P = 0.57). Conclusion: Unmarried patients with ovarian serous carcinoma have higherHRof overall survival. After controlling age, race, grade, radiation and year of diagnosis, unmarried patients were found to have a significantly higher risk of OS. Consequently, these patients are suggested to obtain more focused healthcare for the management of ovarian serous carcinoma.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Marital status; Ovarian serous carcinoma; Overall survival; SEER